Damping Variation Effects in Vehicle Semi-active MR Suspensions: A Stress Concentration Analysis - Vivas-Lopez, Carlos A.; Tudon-Martinez, Juan C.; Estrada-Vela, Alfonso; de Jesus Lozoya-Santos, Jorge; Morales-Menendez, Ruben (Frontiers in Materials, 2021)
Semi-active vehicle suspensions are used to improve the limited comfort performance of passive vehicle suspensions by varying the damping coefficient according to a control strategy. These benefits have been usually studied in a transient and frequency domain, but rarely in a multi-body dynamic analysis considering the mechanical components and their joints. In this study, the controllability effects of a magnetorheological (MR) damper on the mechanical components of a McPherson automotive suspension are investigated using a stress concentration analysis. Finite element analysis was used with a Quarter of Vehicle (QoV) suspension model configured with an MR damper, and then compared with the passive damper. The simulation results show that an SA damper in the suspension not only improves the dynamic behavior of a road vehicle, but it also has the positive effect of reducing the stress concentrations in a critical suspension element, the knuckle, that are generated by high amplitude road profiles such as rough roads or dangerous street bumps.